2022
DOI: 10.3390/nu14132618
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vitamin D Supplementation on the Severity of Symptoms and the Quality of Life in Irritable Bowel Syndrome Patients: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Irritable bowel syndrome (IBS), a gastrointestinal disorder affecting 7–12% of the population, is characterized by abdominal pain, bloating, and alternating bowel patterns. Data on risk and protective influences have yielded conflicting evidence on the effects of alternative interventions, such as vitamin D. This review focuses on the effects of vitamin D on IBS. A systematic review and meta-analysis considered all articles published until 4 April 2022. The search for randomized controlled trials assessing vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 63 publications
0
7
2
Order By: Relevance
“…However, the other randomized, double-blind, placebocontrolled study by Williams et al demonstrated that there were no improvements in the IBS symptom severity and QOL between the trial (Vit-D supplementation) and placebo groups [10]. And, a systematic review and meta-analysis based on 6 randomized controlled trials including 616 participants indicated that Vit-D supplementation had no significant improvements in symptom severity and QOL of IBS subjects in contrast to placebo [26]. Considering that Vit-D contributes to the regulation of the gut microbiome, immune system, inflammatory processes and the intestinal mucosal barrier, the present interventional trials on IBS mainly focused on Vit-D supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the other randomized, double-blind, placebocontrolled study by Williams et al demonstrated that there were no improvements in the IBS symptom severity and QOL between the trial (Vit-D supplementation) and placebo groups [10]. And, a systematic review and meta-analysis based on 6 randomized controlled trials including 616 participants indicated that Vit-D supplementation had no significant improvements in symptom severity and QOL of IBS subjects in contrast to placebo [26]. Considering that Vit-D contributes to the regulation of the gut microbiome, immune system, inflammatory processes and the intestinal mucosal barrier, the present interventional trials on IBS mainly focused on Vit-D supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…This high number of citations in the literature suggests that the most used model in the field of visceral pain research is probably colorectal dilatation, which may lead to changes in bowel perception, forming nociceptive sensitization that eventually evolves into IBS. Indeed, IBS is known to be one of the commonest types of visceral pain ( Abuelazm et al, 2022 ). On this basis, a network map was further constructed for visualization to generate key clusters of co-cited literature and visualization of the timeline of co-cited literature, which were divided into three major clusters, each closely related to the other.…”
Section: Discussionmentioning
confidence: 99%
“…However, the other randomized, double-blind, placebo-controlled study by Williams et al demonstrated that there were no improvements in the IBS symptom severity and QOL between the trial (Vit-D supplementation) and placebo groups [ 15 ]. Moreover, a systematic review and meta-analysis based on six randomized controlled trials including 616 participants indicated that Vit-D supplementation led to no significant improvements in symptom severity and QOL of IBS subjects in contrast to placebo [ 31 ]. Considering that Vit-D contributes to the regulation of the gut microbiome, immune system, inflammatory processes, and the intestinal mucosal barrier, the present interventional trials on IBS mainly focused on Vit-D supplementation.…”
Section: Discussionmentioning
confidence: 99%